Violence against women and the role of gender equality, social inclusion and health strategies - Crepaldi, Chiara; Samek Lodovici, Manuela; Corsi, Marcella (Luxembourg, 2010)
"Although the EU has made significant strides towards achieving gender equality over recent decades, women remain the principal victims of gender-based violence. The European Commission’s Synthesis Report for 2010 on violence against women and the role of gender equality, social inclusion and health strategies analyses the social aspects of such violence. It aims to present a clear picture of the situation in EU Member States, EEA/EFTA and candidate countries regarding all types of violence directed at women, be they physical, sexual or psychological. The report begins by summarising the main features of violence against women in Europe. It then gives an overview of actions addressing this form of violence, in terms of prevention, victim support and social reintegration before presenting its final conclusions and their related policy implications. "